FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI LABA AKUNTANSI DAN IMPLEMENTASINYA TERHADAP KELANGSUNGAN HIDUP PERUSAHAAN PADA SEKTOR ANEKA INDUSTRI - Septony B. Siahaan; Arthur Simanjuntak; Astri Madonna Damanik (Jurnal Ilmu Manajemen METHONOMIX, 2021)
The purpose of this study is to test and analyze the factors that affect the value of accounting profits and their implementation on the company's survival in the multi-industry sector during the period 2016 to 2019. The company's survival in the study used a Price to Book Value (PBV) gauge. While accounting profit as a variable intervening in this study uses the measure Return on Assets (ROA). And Firm Size is measured by Logarithm Natural Total Assets. The sample used was 19 companies from 53 populations of various industrial sector companies listed on the Indonesia Stock Exchange for the period 2016-2019. Number of Observations as many as 76 observation data (19 Companies X 4 Years of Observation). Sampling method using Purposive Sampling. The study used multiple regression analysis and was processed using SPSS 25. The results of this study showed that Firm Size and DER partially had a negative and insignificant influence on ROA, and CR partially had a positive and significant influence on ROA. Firm Size, DER, and CR have a shared influence on ROA. Firm Sizes had a negative significant influence on PBV, Direct influence of DER, and CR had a positive and insignificant influence on PBV. Simultaneously Firm Size, DER, and CR had a significant influence on PBV. The direct influence of ROA has a positive significant influence on the PBV. Based on the results of the path analysis showed that the ROA variable did not successfully mediate or become the intervening variable of the Firm Size variable, DER in influencing the PBV. Based on the results of the path analysis shows that the ROA variable successfully mediated or became an intervening variable of the CR variable in influencing the PBV.